Process evaluation of a workplace-based health promotion and exercise cluster-randomised trial to increase productivity and reduce neck pain in office workers: A RE-AIM approach - Welch, A.; Healy, Genevieve; Straker, Leon; Comans, T.; O'Leary, S.; Melloh, Markus; Sjøgaard, G.; Pereira, M.; Chen, X.; Johnston, V. (2020)
© 2020 The Author(s).